Designing Effective Regulations on Rabies Control in Tropical Regions: A Systematic Literature Review - Ni Putu Meiliana Dewantari; I Nyoman Bagiastra; I Wayan Gede Artawan Eka Putra (Dinasti Research, 2024)
Rabies, a global public health issue with a 100% mortality rate, affects tens of thousands annually, primarily in tropical regions, and is widespread in over 150 regions. Effective rabies control regulations are crucial in tropical regions due to limited healthcare, dense population, and virus-carrying species, promoting well-being, reducing costs, and promoting sustainability. This article aims to design effective regulations on rabies control in tropical regions. The study utilized a systematic literature review to explore effective rabies control in tropical regions. The analysis used Publish and Perish 8 tool and Mendeley Reference Manager software. The PRISMA was employed to guide the investigation. The study identified 26 significant research articles from 357 exclusions. The results reveal that pet rabies regulations may not effectively control outbreaks, requiring prioritizing awareness campaigns due to resource constraints, weak healthcare systems, and cultural factors in tropical regions. Therefore, the design of effective regulations on rabies control in tropical regions highlight: vaccination programs targeting pet domestications; reducing risk of rabies transmission through domesticated livestock; including rules on control, risk regulation, and animal population control; outlining minimum standards for health facilities and veterinary services; retraining healthcare workers and veterinarians involved in rabies prevention is necessary.